Pengaruh Psikologi Konsumen, Kepercayaan, Dan Fasilitas Terhadap Keputusan Konsumen Pengguna Jasa Pada Badan Layanan Umum Unit Pengelola Bandara Udara Djalaludin Gorontalo - Usu, Idrus; Yakup, Yakup; Karundeng, Deby Rita; Hariansyah, Muh. Khaerul Annas (CV. ITTC INDONESIA, 2024)
This research aims to determine and analyze the influence of consumer psychology on facilities and trust on the decision to use air transportation services at the Djalaludin Gorontalo Airport Management Unit Public Services Agency. The quantitative method used in this research is multiple linear regression analysis to analyze the influence of the independent variable on the dependent variable. The research results show that consumer psychology has a positive and significant influence on consumer decisions. Strong consumer psychology will increase the speed of consumer decision making. Trust has a positive and significant effect on consumer decisions. If consumer trust is high in the company, consumer decisions will be faster. Facilities have a positive and significant influence on consumer decisions. The completeness of the facilities will speed up consumers' decisions in choosing which services to use.